Freedom of expression as the constitutional right in Myanmar - Hnin, Nwe Htwe (Đại học Quốc gia Hà Nội, 2020)
Freedom of expression right is an individual right that are recognized under many international conventions and regional conventions. This right is recognized by the International Human Rights Declaration 1948 as a common standard for all peoples and all nations. The Freedom of expression right is also mentioned in the constitutions of every country as a fundamental right of all citizens. In Myanmar, three constitutions were enacted. Myanmar first constitution was enacted in 1947, the second constitution was enacted in 1974 and the present constitution as the third constitution was enacted in 2008. Freedom of expression right recognized as fundamental right of the citizens by all three constitutions. Section 17 of 1947 Constitution of the Socialist Republic of the Union of Myanmar and Section 157 of 1974 Constitution of the Myanmar assured the freedom of expression right as fundamental right. And also Section 354 of the Constitution of the Republic of the Union of Myanmar 2008 mentions that “every citizen shall be at liberty in the exercise of the freedom of expression right, if not contrary to the laws, enacted for union security, prevalence of law and order, community peace and tranquillity or public order and morality”. But the effective enjoyment of adequate protection for freedom of expression right as a constitutional right is still challenging in Myanmar. Although freedom of expression right is a fundamental constitutional right, this right can be limited by enacted law under the Constitution of the Republic of the Union of Myanmar 2008.